0
$\begingroup$

Let $N_t$ be a Poisson process with intensity $\lambda>0$ and $S_t$ follows a pure jump process $$dS_t=S_t(J_t-1)dN_t$$ where $J_t$ is the jump size variable if $N_t$ jumps at time $t$. Also, assume $J_t$ follows a lognormal distribution such that $\ln{ J_t}\sim N(\mu_j,\sigma_j^2)$ and $J_t$ is also independent of $N_t$ . How can we find $Var(S_T| S_t)$ ?

Thanks for any hint.

$\endgroup$
  • 1
    $\begingroup$ Have you tried applying ito's lemma (for discontinuous semi martingales) to $\ln(S_t)$ to find the solution of the SDE? $\endgroup$ – Quantuple Nov 20 '16 at 12:43
  • $\begingroup$ yes but I can't recieve the solution. please add your solution. $\endgroup$ – math Nov 20 '16 at 14:03
  • $\begingroup$ this document might help you better understand the nice answer provided by Behrouz Maleki: google.be/url?sa=t&source=web&rct=j&url=http://… $\endgroup$ – Quantuple Nov 20 '16 at 21:49
5
$\begingroup$

Hint:

By application of Extended Ito's lemmma, we have $$d(\ln S_t)=\sum_{n=1}^{\infty}\frac{(-1)^{n+1}}{n}\left(\frac{dS_t}{S_{t^-}}\right)^n\tag 1$$ Note $S_{t^-}$ denote the value of $S_t$ before a jump event. We know $d[N_t,N_t]=dN_t$, thus $$d(\ln S_t)=\sum_{n=1}^{\infty}\frac{(-1)^{n+1}}{n}(J_t-1)^n=\left(\ln{J_t} \right)dN_t\tag 2$$ By taking integrals on $[t,T]$, we have $$\int_{t}^{T}d(\ln S_u)=\int_{t}^{T}\left(\ln{J_u} \right)dN_u\tag 3$$ therefore $$\ln\left(\frac{S_T}{S_t}\right)=\sum_{n=1}^{N_{T-t}}\ln J_n\tag 4$$ in other words $$S_T=S_t\prod_{n=1}^{N_{T-t}}J_n\tag 5$$ Note $J_n \in (0, 2]$ is the jump size occurring at time instant $t_n$. Also $N_{T-t}=N_T-N_t$ is the total number of jumps in the time interval $(t,T]$. Since $\ln J_n\sim \mathcal{N}(\mu_J,\sigma^2_J)$ are independent and identically distribute, $\ln S_T=\ln S_t+\sum_{n=1}^{N_{T-t}}\ln J_n$ follows a normal distribution.Now apply equation $(5)$ $$\text{Var}\left(S_T\Big{|}S_t\right)=\text{Var}\left(S_t\prod_{n=1}^{N_{T-t}}J_n\Big{|}S_t\right)=S_t^2\,\text{Var}\left(\prod_{n=1}^{N_{T-t}}J_n\right)\\=S_t^2\,\text{Var}\left(\exp\left(\sum_{n=1}^{N_{T-t}}\ln J_n\right)\right)\\ $$ then $$\text{Var}\left(S_T\Big{|}S_t\right)=S_t^2\left(\underbrace{\mathbb{E}\left[\exp\left(\sum_{n=1}^{N_{T-t}}\ln J_n^2\right)\right]}_{I}-\underbrace{\mathbb{E}\left[\exp\left(\sum_{n=1}^{N_{T-t}}\ln J_n\right)\right]^2}_{J}\right)\tag 6$$ Note $$I=\mathbb{E}\left[\mathbb{E}\left[\exp\left(\sum_{n=1}^{N_{T-t}}\ln J_n^2\right)\right]\Big{|}N_{T-t}\right]=\exp\left(\lambda(T-t)(E[J_t^2]-1)\right)\\I=\exp\left(\lambda(T-t)e^{2\mu_J+2\sigma_J^2}-\lambda(T-t)\right)\tag 7$$ similarly $$J=\mathbb{E}\left[\mathbb{E}\left[\exp\left(\sum_{n=1}^{N_{T-t}}\ln J_n\right)\right]\Big{|}N_{T-t}\right]^2=\exp\left(2\lambda(T-t)e^{\mu_J+\frac 12\sigma_J^2}-2\lambda(T-t)\right)\tag 8$$ $(6)$, $(7)$ and $(8)$ $$\color{red}{\text{Var}\left(S_T\Big{|}S_t\right)=S_t^2\exp\left(\lambda(T-t)e^{2\mu_J+2\sigma_J^2}-\lambda(T-t)\right)\\\qquad\qquad\quad\quad -S_t^2\exp\left(2\lambda(T-t)e^{\mu_J+\frac 12\sigma_J^2}-2\lambda(T-t)\right)}$$

$\endgroup$
  • $\begingroup$ Thanks but your solution is so hard. May you insert some details? $\endgroup$ – math Nov 20 '16 at 14:04
  • 4
    $\begingroup$ @math you are already lucky he took the time to develop all this given the fact you showed none of your effort in your question. $\endgroup$ – SRKX Nov 20 '16 at 14:58
  • $\begingroup$ @math I think my solution is clear and easy. $\endgroup$ – user16651 Nov 20 '16 at 15:12
  • $\begingroup$ @SRKX I tried, but unfortunately I didn't solve my question.There is some complexities in Behrouz's solution $\endgroup$ – math Nov 20 '16 at 16:00
  • $\begingroup$ @math lots of clarifications were added, but if you're still struggling with something, be specific. $\endgroup$ – SRKX Nov 20 '16 at 16:05
1
$\begingroup$

Alternatively, let $\{\tau_i\}_{i=1}^{\infty}$ be the jump time of the Poisson process $N$. Moreover, let \begin{align*} X_t = \int_0^t (J_s-1)dN_s. \end{align*} Here, we assume that the jump sizes $J(\tau_i)$, for $i=1, \ldots, \infty$, are independent identically distributed. Then, \begin{align*} X_t &= \sum_{0<s\le t}(J_s-1)1_{\Delta N(s) >0}. \end{align*} Note that \begin{align*} dS_t = S_{t-} dX_t, \end{align*} whose solution is the Doleans-Dade exponential, that is, \begin{align*} S_t &= S_0 \prod_{0 < s \le t} (1+ \Delta X_s)\\ &=S_0 \prod_{0 < s \le t} J_s 1_{\Delta N(s) >0}\\ &=S_0\prod_{i=1}^{N_t}J(\tau_i). \end{align*} For $T>t \ge 0$, \begin{align*} S_T &= S_t \prod_{i=N_t+1}^{N_T}J(\tau_i)\\ &= S_t \prod_{i=1}^{N_T-N_t}J(\tau_i) \quad \text{(in distribution)}\\ &= S_t \prod_{i=1}^{N_{T-t}}J(\tau_i) \quad \text{(in distribution)}. \end{align*} The remaining is the same as that of @Behrouz Maleki above.

$\endgroup$
  • $\begingroup$ A nice approach +1 $\endgroup$ – user16651 Nov 21 '16 at 14:30

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.